A dynamical model of the spindle position checkpoint - Caydasi, Ayse Koca; Pereira, Gislene (Molecular systems biology, 2012)
The orientation of the mitotic spindle with respect to the polarity axis is crucial for the accuracy of asymmetric cell division. In budding yeast, a surveillance mechanism called the spindle position checkpoint (SPOC) prevents exit from mitosis when the mitotic spindle fails to align along the mother‐to‐daughter polarity axis. SPOC arrest relies upon inhibition of the GTPase Tem1 by the GTPase‐activating protein (GAP) complex Bfa1-Bub2. Importantly, reactions signaling mitotic exit take place at yeast centrosomes (named spindle pole bodies, SPBs) and the GAP complex also promotes SPB localization of Tem1. Yet, whether the regulation of Tem1 by Bfa1-Bub2 takes place only at the SPBs remains elusive. Here, we present a quantitative analysis of Bfa1-Bub2 and Tem1 localization at the SPBs. Based on the measured SPB‐bound protein levels, we introduce a dynamical model of the SPOC that describes the regulation of Bfa1 and Tem1. Our model suggests that Bfa1 interacts with Tem1 in the cytoplasm as well as at the SPBs to provide efficient Tem1 inhibition. Synopsis: The spindle position checkpoint (SPOC) is an important surveillance mechanism in the budding yeast cell cycle. An integrated approach, combining quantitative experimental cell biology with mathematical modeling, reveals how the SPOC inhibits mitotic exit at the molecular level. We used fluorescence microscopy to quantify the number of molecules of Bfa1, Bub2 and Tem1 at the spindle pole bodies, and the size of the GAP‐dependent and ‐independent Tem1 pools that coexist during mitosis.We constructed a dynamical model of Tem1 regulation by Bfa1-Bub2.Based on in‐silico evidence supported by in‐vivo data, we propose that cytoplasmic regulation of Tem1 by the GAP complex is critical for robust spindle position checkpoint arrest.Our model also indicates the necessity of additional mechanisms of GAP inhibition for checkpoint silencing after spindle realignment.